Isothermal crystallization kinetics of refined palm oil - Chen, C. W.; Lai, O. M.; Ghazali, H. M.; Chong, C. L. (Wiley, 2002)
The induction times for the crystallization, under isothermal conditions, of refined, bleached, and deodorized palm oil from the melt were studied by viscometry. At temperatures below 295 K, the crystallization of palm oil was observed to occur in a two‐stage process. This two‐stage process was caused by the fractionation of palm oil, most probably into the stearin and olein fractions. At temperatures higher than 295 K, only a single‐stage crystallization process was observed. As seen under polarized light microscopy, spherical crystals were initially formed from the first fraction at temperatures from 287 to 293 K. The diameters of these spherical crystals decreased as the temperature increased. After that, needle‐shaped crystals were formed from the second fraction and continued to grow from the surface of these spherical crystals until the spherical crystals were fully enclosed, i.e., the cocrystallization of two polymorphs was observed. At temperatures higher than 293 K, the needle‐shaped crystals formed from a mixture of the two fractions were found to be the only polymorphs developed with the onset of crystallization. X‐ray diffraction results showed that for temperatures below 295 K, the spherical crystals formed from the first fraction were in α form, whereas the needle‐like crystals that nucleated later from the second fraction were in β′ form. β′ crystals were the only polymorphs formed for temperatures above 295 K. The results obtained were in good agreement with the discontinuity observed in the induction time vs. temperature curve. Activation free energies for nucleation were calculated according to the Fisher‐Turnbull equation for the various polymorphic forms. Viscometry was observed to be a sensitive method for characterizing the overall crystallization process. This technique is suitable for induction time studies of palm oil crystallization, especially at lower temperatures and with viscous oil.